2018
DOI: 10.13064/ksss.2018.10.1.009
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic correlates of L2 English stress ― Comparison of Japanese English and Korean English*

Abstract: This study compared the relative contributions of intensity, F0, duration and vowel spectra of L2 English lexical stress by Japanese and Korean learners of English. Recordings of Japanese, Korean and native English speakers reading eighteen 2 to 4 syllable words in a carrier sentence were analyzed using multiple regression to investigate the influence of each acoustic correlate in determining whether a vowel was stressed. The relative contribution of each correlate was calculated by converting the coefficients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…Regarding morphology, higher L2 proficiency promoted the processing of L2-derived and inflected words, new valid derivations, and forms combining a real stem with a new suffix (Kimppa et al, 2019). Concerning phonology, higher L2 proficiency inhibited L1 lexical activation (Berghoff et al, 2021), facilitated the distinction of L2 phonemic contrasts (White et al, 2015), and increased monolingual-like pronunciation (Maddah and Reiterer, 2018), intonation (Jun and Oh, 2000) and stress (Konishi et al, 2018). Furthermore, neural representations change with L2 proficiency (see , for a review) and higher proficiency L2 learners activate the same areas in the brain as monolinguals (Vingerhoets et al, 2003).…”
Section: The Role Of Aoo Proficiency and Use On Bilingual Language Pr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding morphology, higher L2 proficiency promoted the processing of L2-derived and inflected words, new valid derivations, and forms combining a real stem with a new suffix (Kimppa et al, 2019). Concerning phonology, higher L2 proficiency inhibited L1 lexical activation (Berghoff et al, 2021), facilitated the distinction of L2 phonemic contrasts (White et al, 2015), and increased monolingual-like pronunciation (Maddah and Reiterer, 2018), intonation (Jun and Oh, 2000) and stress (Konishi et al, 2018). Furthermore, neural representations change with L2 proficiency (see , for a review) and higher proficiency L2 learners activate the same areas in the brain as monolinguals (Vingerhoets et al, 2003).…”
Section: The Role Of Aoo Proficiency and Use On Bilingual Language Pr...mentioning
confidence: 99%
“…Behavioral L2 studies revealed that higher L2 proficiency facilitated L2 prediction based on morphosyntactic associations (e.g., Sagarra et al, 2021;Henry et al, 2022;see Ito and Pickering, 2021, for a review; and see Mitsugi, 2020, for lack of proficiency effects), phonosemantic associations (Perdomo and Kaan, 2021, for bin 5), and morphophonological associations (Sagarra and Casillas, 2018). Higher L2 proficiency also benefited L2 morphosyntactic processing (see 10.3389/fpsyg.2023.1141174 Frontiers in Psychology 14 frontiersin.org Kirova and Camacho, 2021, for a review), as well as L2 morphological processing (Kimppa et al, 2019), L2 word activation (Berghoff et al, 2021), and L2 phonological processing (Jun and Oh, 2000;White et al, 2015;Konishi et al, 2018;Maddah and Reiterer, 2018). Neurocognitive L2 studies indicated that higher L2 proficiency facilitated L2 morphosyntactic processing (see Alemán , for a review) and shaped the brain , allowing learners to activate the same brain areas as monolinguals (Vingerhoets et al, 2003).…”
Section: The Effects Of Language Proficiencymentioning
confidence: 99%
“…Regarding morphology, higher L2 proficiency promoted the processing of L2-derived and inflected words, new valid derivations, and forms combining a real stem with a new suffix ( Kimppa et al, 2019 ). Concerning phonology, higher L2 proficiency inhibited L1 lexical activation ( Berghoff et al, 2021 ), facilitated the distinction of L2 phonemic contrasts ( White et al, 2015 ), and increased monolingual-like pronunciation ( Maddah and Reiterer, 2018 ), intonation ( Jun and Oh, 2000 ) and stress ( Konishi et al, 2018 ). Furthermore, neural representations change with L2 proficiency (see Pliatsikas et al, 2020 , for a review) and higher proficiency L2 learners activate the same areas in the brain as monolinguals ( Vingerhoets et al, 2003 ).…”
Section: The Role Of Aoo Proficiency and Use On Bilingual Language Pr...mentioning
confidence: 99%
“…Behavioral L2 studies revealed that higher L2 proficiency facilitated L2 prediction based on morphosyntactic associations (e.g., Lew-Williams and Fernald, 2010;Dussias et al, 2013;Sagarra et al, 2021;Henry et al, 2022;see Ito and Pickering, 2021, for a review; and see Mitsugi, 2020, for lack of proficiency effects), phonosemantic associations (Perdomo and Kaan, 2021, for bin 5), and morphophonological associations (Sagarra and Casillas, 2018). Higher L2 proficiency also benefited L2 morphosyntactic processing (see 10.3389/fpsyg.2023.1141174 Frontiers in Psychology 14 frontiersin.org Kirova and Camacho, 2021, for a review), as well as L2 morphological processing (Kimppa et al, 2019), L2 word activation (Berghoff et al, 2021), and L2 phonological processing (Jun and Oh, 2000;White et al, 2015;Konishi et al, 2018;Maddah and Reiterer, 2018). Neurocognitive L2 studies indicated that higher L2 proficiency facilitated L2 morphosyntactic processing (see Alemán Bañón et al, 2018, for a review) and shaped the brain (Pliatsikas et al, 2020), allowing learners to activate the same brain areas as monolinguals (Vingerhoets et al, 2003).…”
Section: The Effects Of Language Proficiencymentioning
confidence: 99%
“…Studies show that higher L2 proficiency facilitates L2 phonological and morphological processing. First, concerning L2 proficiency effects on L2 phonological processing, higher L2 proficiency decreases L1 lexical activation (Berghoff et al, 2021) reduces L1 influence on L2 intonation (Jun & Oh, 2000), L2 stress (Konishi et al, 2018), and L2 pronunciation and vowel duration (Maddah & Reiterer, 2018), and eases the distinction of L2 phonemic contrasts in implicit tasks (White et al, 2015). Regarding L2 proficiency effects on L2 processing of inflectional morphology, higher L2 proficiency promotes L2 morphosyntactic processing (see Alemán Bañón et al, 2018, for a review), as well as sensitivity to L2 verbal agreement violations (lower proficiency learners are insensitive, Sagarra, 2014) or show delayed sensitivity, Rossi et al, 2006, whereas higher proficiency learners are sensitive, Yao & Chen, 2017).…”
Section: Effects Of L2 Proficiency and Use On L2 Phonological And Mor...mentioning
confidence: 99%